Overview of Admixture Mapping. Issue 2 (14th February 2023) - Shriner, Daniel
Abstract: Admixture mapping is a powerful method of gene mapping for diseases or traits that show differential risk by ancestry. Admixture mapping has been applied most often to Americans who trace ancestry to various combinations of Native Americans, Europeans, and West Africans. Recent developments in admixture mapping include improvements in the methods and reference data needed to make inferences about ancestry as well as extensions of the mapping approach in the framework of linear mixed models. This overview outlines the key concepts of admixture mapping. It describes approaches for inferring local ancestry and provides strategies for performing admixture mapping depending on the study design. Finally, linkage analysis, association analysis, and admixture mapping are compared, with an emphasis on integrating admixture mapping and association testing. Published 2023. This article is a U.S. Government work and is in the public domain in the USA.